An Analyzing Teacher’s Interactional Strategies in Classroom Discourse: A Study at MAS Hidayatul Quran Puding Besar - Hairul Hairul; Rahma Aini (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2026)
Interaction plays an important role in supporting language learning, especially in developing students’ classroom interaction. This study aimed to analyze the teacher’s interactional strategies in classroom discourse at MAS Hidayatul Quran Puding Besar. The participants were one of English teacher and 26 students of Grade XII IPA (Science). The data were collected through classroom observation during 2x45 minutes for 2 meetings and analyzed by using Walsh’s (2006) SETT Framework. The study used a qualitative approach to interpret the classroom discourse and a quantitative approach to describe the frequency of strategies.  The result showed that the teacher performed interaction strategies Display Question, Teacher Echo, and Extended-teacher Turn as the most frequently used. Extended-learner Turn, Confirmation Checks, Content Feedback, and Seeking Clarification were interaction strategies occasionally used. These findings imply that the teacher needs to use more interactional strategies to promote longer response and meaningful classroom talk.